Nigeria National Policies and Strategies (NPS) Capacity Sharing Workshops Series: Building a Nigeria Social Accounting Matrix (SAM) - CGIAR (CGIAR System Organization, 2023)
Following the previous CGIAR National Policies and Strategies for Food, Land and Water Systems Transformation (NPS) Initiative[1] capacity workshops in July and September 2022, The International Food Policy Research Institute (IFPRI) held its third training workshop with the Nigerian Institute of Social and Economic Research (NISER) and the National Bureau of Statistics (NBS) on “Building a Nigerian Social Accounting Matrix (SAM)”, from 30th January to 2nd February 2023.